2009
DOI: 10.1002/esp.1773
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of solifluction rates using multi‐temporal aerial photography

Abstract: A new method is presented to assess decadal solifluction lobe movement and volumetric changes at the catchment scale. The method is based on photogrammetrical analysis of orthorectified repeat aerial photography in a geographic information system (GIS). High resolution aerial photographs from two valleys in northern Sweden, Kärkevagge and Låktatjåkka valleys, are used to quantify changes of the lobe fronts, as an indication of solifluction rates over a period of 41 years. Two methods are explored, the flow dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The Låktatjåkka valley, oriented parallel to the Kärkevagge valley, has shorter slopes and a relatively flat east-facing slope. Solifluction landforms are generally smaller and less common in this valley, but at its southern upslope end classical lobe-shaped solifluction features are present (Ridefelt et al 2009 -2008). For location of the two weather stations, see Figure 2 are stone-banked lobes, non-sorted stripes and nonsorted sheets (Ridefelt et al unpublished data).…”
Section: Study Areamentioning
confidence: 92%
See 1 more Smart Citation
“…The Låktatjåkka valley, oriented parallel to the Kärkevagge valley, has shorter slopes and a relatively flat east-facing slope. Solifluction landforms are generally smaller and less common in this valley, but at its southern upslope end classical lobe-shaped solifluction features are present (Ridefelt et al 2009 -2008). For location of the two weather stations, see Figure 2 are stone-banked lobes, non-sorted stripes and nonsorted sheets (Ridefelt et al unpublished data).…”
Section: Study Areamentioning
confidence: 92%
“…Regarding the validity of the movement rates, quantification by photo analysis for the period 1959 to 2000 of the total cumulative movement of a lobe, located at about a hundred metres from lobe 11, provides an independent assessment of lobe movement (Ridefelt et al 2009). The results are very similar in magnitude to those obtained by Rapp and Åkerman (1993) and Åkerman's (unpublished) lobe 11 during the period 1961 to 2002.…”
Section: The Temporal Variationsmentioning
confidence: 99%
“…Repeated freeze-thaw cycles trigger various types of mass movements on periglacial slopes, with solifluction being the most widespread slope-deforming process (Kinnard and Lewkowicz 2005;Ridefelt et al 2009). Although solifluction rates are generally limited to a few centimetres per year, they are, in the long term, the dominant mechanism of slope modification in periglacial environments (Åkerman 1996), thereby contributing greatly to the evolution of periglacial landscapes (Matsuoka 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ridefelt et al . () found that wetness together with altitude were the main controls on the spatial variation of solifluction within an area of uniform bedrock in northern Swedish Lapland. An increase in catchment wetness would thus increase solifluction and thereby generate more sediment deposition in the lake.…”
Section: Erosional Regimes Of Vuoksjávrátje Catchment and Lake Sedimementioning
confidence: 97%